Effects of Mixed H2O-CH3CN solvents on the rate of Hydrazinolysis of N-Phenylphthalimide: spectral and kinetic evidence for The occurrence Of N-Aminophthalimide on the reaction path - Ariffin, Azhar; Khan, M.N.; Lan, L.C.; Leng, S.Y. (2005)
Kinetic study on the cleavage of N-phenylphthalimide (NphPT) in the presence of 0.05 M NH2NH2 and mixed H2O-CH3CN solvents reveals the occurrence of reaction scheme GRAPHICS where A, B, C, C-1, An, E, and F represent NPhPT, o-CO2-C6H4CONHC6H5, o-CONHNH2C6H4-CONHC6H5, N-aminophthalimide, aniline, o-CO2-C6H4CONHNH2, and o-CONHNH2C6H4-CONHNH2, respectively. But, in the presence of either nonbuffered greater than or equal to -0.20 M NH2NH2 or hydrazine buffer of pH similar to 7.30-8.26 with total buffer concentration (\Buf\(T)) of >0.02 M, further conversion of Fto 2,3-dihydrophthalazine-1,4-dione(DHPD) has been detected depending upon the length of the reaction time (t), the values of \Buf\(T), and pH. It has been shown that the rate of conversion of C, to F is much faster than that of C to C, which is much faster than that of F to DHPD. The reaction step A --> C involves general base (GB) catalysis, while step C --> C-1 seems to involve specific base-general acid (GA) and GB-GB catalysis. (C) 2005 Wiley Periodicals, Inc.